2023
DOI: 10.1101/2023.01.15.524095
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Gastrodin ameliorates synaptic impairment, reestablishes mitochondrial membrane potential and reduces oxidative stress in N2a/APP cells through ERK1/2 and GSK-3β pathways

Abstract: Alzheimer's disease (AD) is featured by abnormal &beta-amyloid (Abeta) deposition, neurofibrillary tangle formation, downstream mitochondrial dysfunction, oxidative stress, and synaptic loss. Gastrodin, a phenolic glycoside, has shown neuroprotective effect and used in the treatment of a range of brain diseases. Here we aim to assess the mechanisms and signaling pathways involved in the neuroprotective effect of gastrodin in murine neuroblastoma N2a cells expressing human Swedish mutant amyloid precursor p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 94 publications
0
1
0
Order By: Relevance
“…Several experimental and pharmacological studies indicated that gastrodin could be implemented to alleviate the symptoms and progression of Alzheimer's disease. Indeed, Tang et al [97] conducted a study to explore the effect of gastrodin on ameliorating synaptic impairment, Amyloid precursor protein processing, mitochondrial dysfunction, and oxidative stress damage in a cell model of Alzheimer's disease (N2a/APP). The results showed that treatment with gastrodin elevated presynaptic SNAP25 levels, synaptophysin, and postsynaptic PSD95, decreased phosphorylated tau protein Ser396, and APP-CTFs in N2a/APP cells.…”
Section: Alzheimer's Disease (Ad)mentioning
confidence: 99%
“…Several experimental and pharmacological studies indicated that gastrodin could be implemented to alleviate the symptoms and progression of Alzheimer's disease. Indeed, Tang et al [97] conducted a study to explore the effect of gastrodin on ameliorating synaptic impairment, Amyloid precursor protein processing, mitochondrial dysfunction, and oxidative stress damage in a cell model of Alzheimer's disease (N2a/APP). The results showed that treatment with gastrodin elevated presynaptic SNAP25 levels, synaptophysin, and postsynaptic PSD95, decreased phosphorylated tau protein Ser396, and APP-CTFs in N2a/APP cells.…”
Section: Alzheimer's Disease (Ad)mentioning
confidence: 99%